2013
DOI: 10.17675/2305-6894-2013-2-4-277-286
|View full text |Cite
|
Sign up to set email alerts
|

Volatile inhibitors of atmospheric corrosion of ferrous and nonferrous metals. V. Study of the adsorption of inhibitors on steel from an aqueous electrolyte solution

Abstract: Adsorption of ten Mannich and Schiff bases on steel from a mixed electrolyte solution (30 mg/dm 3 NaCl + 50 mg/dm 3 Na 2 SO 4 ) was studied. The adsorption isotherms show linear segments in the medium coverage range, which may be equally attributed to both the Frumkin and Temkin isotherms. Unfortunately, experimental data are insufficient to distinguish among them. It was demonstrated that the mechanism of action of the inhibitors in vapor phase differs from that in a model electrolyte solution and that testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In this work, two inhibitors of different chemical composition were selected as corrosion inhibitors. Inhibitor VNH-L-113 (1-morpholinomethylcyclohexylamine), belongs to Schiff bases, which are known as corrosion inhibitors in neutral [7] and acidic [8] media. Inhibitor SNPKh-1004 is often used in the practice of corrosion protection in the oil and gas industry [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, two inhibitors of different chemical composition were selected as corrosion inhibitors. Inhibitor VNH-L-113 (1-morpholinomethylcyclohexylamine), belongs to Schiff bases, which are known as corrosion inhibitors in neutral [7] and acidic [8] media. Inhibitor SNPKh-1004 is often used in the practice of corrosion protection in the oil and gas industry [9].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that the limiting stage of anodic dissolution is the incorporation of metal ions into the structure of the near-electrode layer of water molecules [5]. When organic inhibitors are added to the electrolyte, they are adsorbed at the metal -electrolyte interface [6], which leads to a decrease in the double layer capacitance due to a decrease in the dielectric constant. As a result, iron ions formed during anodic dissolution, are introduced into the medium with a dielectric constant lower than water, which leads to an increase in the activation energy of the electrochemical reaction of anodic dissolution [7]:…”
Section: Resultsmentioning
confidence: 99%
“…Variation of vapour pressure (p 0 ) with latent heat of sublimation for DICHAN, cyclohexylamine benzoate and di-isopropylamine nitrile are presented in Figure 1 [46,47,53]. Altsybeeva et al [54,55] studied the action mechanism of volatile inhibitors having different vapour pressure but did not get any regular trend. Further, it was also discussed about the kinetics of VCIs from the surface of various metals, action mechanism and higher inhibition efficiency upon electrostatic application.…”
Section: Effect Of Temperature On Vapour Pressurementioning
confidence: 99%
“…The trend and technology has allowed new methods for a range of VCI applications to be reliably extended into new areas of applications. The corrosion protection in oil & gas, military, automotive, electronic, electrical, and other industrial sectors see existing and new technologies which increase efficiency and service life and decrease the total cost [74][75][76].…”
Section: Vci As Corrosion Inhibitors For Ferrous Materialsmentioning
confidence: 99%